PENGGUNAAN PEREKAT SEBAGAI ALAT SAMBUNG PADA KONSTRUKSI SAMBUNGAN KAYU - Darmono Darmono (Universitas Negeri Yogyakarta, 2006)
This research aims: (1) to observe the strength of wood join using adhesive in holding up the shearing load, (2) to observe the difference of shear strength of wood join using adhesive of several trademarks: GG, ZZ, FF, RR, and PP.This is an experimental research conducted in the Construction MaterialTesting Laboratory, the Department of Civil Engineering and Planning Education, FT UNY. Five trademarks of adhesive are used: GG, ZZ, FF, RR, and PP, 10 samples for each trademark of adhesive. The total samples of this research are therefore 50. The data analysis technique to reject or accept the hypothesis uses the one way variant analysis. The test requirements for one way variant analysis are: (1) normality test and (2) homogeneity test. The research results show that: (1) the mean of shear strength of wood join using the adhesive of GG is 14 kg/cm2, adhesive ZZ is 16,64 kg/cm2 , adhesive FF is 20 kg/cm2 , adhesive RR is 22,64 kg/cm2 , and adhesive PP is 37,82 kg/cm2• (2) There is a significance difference among shear strength ofwood join using the adhesives of GG, ZZ, FF, RR, and PP. (3) The comparison result of the economical values viewed by the adhesive trademarks from the most to the least economical ones are FF, PP, RR,GG, and ZZ. (4) The comparison results of the adhesive characteristics from the most brittle to the most elastic ones are respectively RR, PP, FF, GG, and ZZ. (5) The comparison results of the cohesion power from the highest to the lowest ones are respectively RR, ZZ, PP, GG, and FF. Key words: adhesive, joining material, and wood.